A rare case of scrotal basal cell carcinoma in the presence of metastatic squamous cell carcinoma of the external auditory meatus and its management strategy - Tan, Guan Hee; Elsa JR,; Fam, XI; Shukor NA,; Goh, Eng Hong; Praveen Singam,; Ho, CCK; Zulkifli Md. Zainuddin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Basal cell carcinoma (BCC) of the scrotum is uncommon and its pathogenesis is not well understood. The clinical behaviour of scrotal BCC is thought to be more aggressive and has a higher metastatic potential than BCC of other regions. The mainstay of treatment for localized scrotal BCC is wide local excision, while metastatic disease may need systemic chemotherapy for palliative control. A rare clinical scenario of scrotal BCC presenting concurrently with another metastatic cancer has never been reported. The present case illustrates the diagnostic challenge and management dilemma due to simultaneous presentation of scrotal BCC and metastatic squamous cell carcinoma (SCC). A 70-year-old man complained of a non-healing scrotal ulcer while he was being investigated for metastatic squamous cell carcinoma (SCC) of the external auditory meatus. The scrotal lesion was initially thought to be metastatic SCC. It was later confirmed to be BCC with biopsy and histopathological examination. He underwent surgical resection of the scrotal BCC for local control followed by palliative chemotherapy with cisplatin and radiotherapy for lymph node metastases. He remained well and did not have any local recurrence following 6 months after palliative treatment. Surgery coupled with palliative chemoradiation can offer good quality of life for patients with scrotal BCC and concurrent metastatic SCC.